Synthesis of Dibenzophosphole Oxides via Palladium‐Catalyzed Intramolecular Direct Arylation Reactions of ortho‐Halodiarylphosphine Oxides. Issue 6 (20th March 2014) - Cui, Yuming; Fu, Lingzi; Cao, Jian; Deng, Yuan; Jiang, Jianxiong
Abstract A palladium‐catalyzed intramolecular direct arylation reaction was developed and two efficient one‐pot sequential direct arylation/Suzuki–Miyaura coupling and intra/intermolecular direct arylation reations were also realized. The method provides a simple and straightforward procedure for the synthesis and further functionalization of dibenzophosphole oxides from easily accessible ortho‐halodiarylphosphine oxides in good to excellent yields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>